How do mutations thermostabilize G protein-coupled receptors? - Vaidehi, Nagarajan (Trends Pharmacol Sci, 2015)
Structures of over 30 different G protein-coupled receptors (GPCRs) have advanced our understanding of cell signaling and provided a foundation for structure-guided drug design. This exciting progress required the development of three complimentary methods to facilitate GPCR crystallization, one of which is the thermostabilization of receptors by systematic mutagenesis. However, the reason why a particular mutation, or combination of mutations, stabilizes the receptor is not always evident from a static crystal structure. Molecular dynamics simulations have been used to identify and estimate the energetic factors that affect thermostability through comparing the dynamics of the thermostabilized receptors with structure-based models of the wild-type receptor. The data indicate that receptors are stabilized through a combination of factors, including an increase in receptor rigidity, a decrease in collective motion, reduced stress at specific residues, and the presence of ordered water molecules. Predicting thermostabilizing mutations computationally represents a major challenge for the field.